ANALISIS KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN KESEHATAN KEPADA PASIEN DI PUSKESMAS PEMBINA KELURAHAN SILABERANTI KOTA PALEMBANG - H. A. Rizal Fahlevi (STIA SATYA NEGARA PALEMBANG, 2022)
Public services are the responsibility of the government and are carried out by government agencies, both at the center, in the regions, and in the environment of State-Owned Enterprises. Public services are in the form of public goods and services. Today the public is increasingly open in providing criticism for public services. Therefore the administrative substance is very instrumental in regulating and directing all activities of the service organization in achieving its objectives.The research method used in this thesis used is qualitative research with descriptive research type, which is a study that aims to provide a factual picture with the right arguments. Therefore, this study aims to obtain a picture through an analysis process to understand the analysis of employee performance in providing health services to patients at the Puskesmas Pembina Kelurahan Silaberanti Palembang City.From the results of the study found the performance of employees in providing health services to patients in the Puskesmas Pembina Silaberanti Kelurahan Palembang City still needs to be improved because the Puskesmas Pembina employees come to work not on time with the Operational Puskesmas Pembina standards at 7.30 WIB, so patients at Puskesmas Pembina feel not served well and professionally in carrying out patient health services. Factors that hinder the performance of employees in providing health services to patients in Puskesmas Silaberanti Palembang City are employee attitudes, work rules that are violated, piling up work, work accuracy, work motivation and special service information. Keywords: Employee performance, health services